Diagnostic yield of fourth‐generation endocytoscopy for esophageal squamous lesions using a modified endocytoscopic classification. Issue 7 (19th January 2021) - Shimamura, Yuto; Inoue, Haruhiro; Rodriguez de Santiago, Enrique; Abad, Mary Raina Angeli; Fujiyoshi, Yusuke; Toshimori, Akiko; Tanabe, Mayo; Sumi, Kazuya; Iwaya, Yugo; Ikeda, Haruo; Onimaru, Manabu; Kushima, Miki; et al.
Abstract : Objectives: Endocytoscopy (EC) is an ultra‐high magnification endoscopy designed to provide in vivo histologic assessment. This study aimed to evaluate the diagnostic yield of the newly developed fourth‐generation EC for esophageal squamous lesions by using a modified EC classification. Methods: A total of 2548 EC images of 57 esophageal targeted areas between June 2015 and October 2017 were retrospectively collected. Two lesions with low‐quality images were excluded. Only EC images were independently reviewed by two expert and two non‐expert endoscopists. The lesions were classified according to a three‐tier modified EC classification. We used a multilevel logistic regression to analyze the data. Results: The sensitivity and specificity of diagnosing non‐squamous cell cancer (SCC) vs SCC were 82.5% and 83.0% by the experts; 90.1% and 75.0% by non‐experts. The interobserver agreement among the four raters was good (kappa statistic 0.59). The diagnostic accuracy of experts and non‐experts was similar ( P  = 0.16 for specificity and P  = 0.20 for sensitivity). The sensitivity and specificity of EC for non‐neoplasia vs neoplasia were 88.7% and 74.6% by experts; 90.3 and 52.1% by non‐experts. The interobserver agreement among the four raters was moderate (kappa statistic 0.44). The specificity of experts was higher compared to non‐experts, although the difference did not reach statistical significance ( P  = 0.08 for specificity and P  = 0.93 for sensitivity). Conclusions: Fourth‐generation EC offers acceptable diagnostic accuracy and reliability in both experts and non‐experts, especially when diagnosing SCC lesions.